MAKING RELATIONSHIP WITH THE SUCCESS OF BROILER CONTRACT FARMING AT TABANAN REGENCY - MAHARDIKA C. B. D. P.; I N. SUPARTA; N. W. T. INGGRIATI (Majalah Ilmiah Peternakan, 2018)
This research aims at determining the successful level of broiler contract farming and management decisionmakingability. In addition, it was also conducted with the correlation of knowledge, attitude, motivation, perceptionand social interaction of farmers with the success of decision making and broiler contract farming. The researchwas carried out at Tabanan regency. There were 122 farmers as respondents using proportionate stratified randomsampling and analyzed using by SEM-PLS. It showed that the successful level of broiler contract farming on middlelevel and most of farmers have abilities to make a good decision on broiler management. Knowledge, attitudeand perception have positive significantly for decision making of broiler management, but motivation and socialinteraction had not significantly effected. Decision making gave positive effect to the success broiler contractfarming.